Subjective Lives and Economic Transformations in Mongolia Life in the Gap - Empson, Rebecca M. (Economic Exposures in Asia, 2020)
Almost 10 years ago the mineral-rich country of Mongolia experienced very rapid economic growth, fuelled by China's need for coal and copper. New subjects, buildings, and businesses flourished, and future dreams were imagined and hoped for. This period of growth is, however, now over. Mongolia is instead facing high levels of public and private debt, conflicts over land and sovereignty, and a changed political climate that threatens its fragile democratic institutions. Subjective Lives and Economic Transformations in Mongolia details this complex story through the intimate lives of five women. Building on long-term friendships, which span over 20 years, Rebecca documents their personal journeys in an ever-shifting landscape. She reveals how these women use experiences of living a 'life in the gap' to survive the hard reality between desired outcomes and their actual daily lives. In doing so, she offers a completely different picture from that presented by economists and statisticians of what it is like to live in this fluctuating extractive economy.